The acquisition of real estate by timesharing contract in Europe - Papp, Tekla (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Timeshare agreement is a contract that aims to the acquisition of the right to use an accommodation for a period of time on a rotating basis and according to this agreement the consumer, in return for consideration, directly or indirectly acquires the right from the marketer for more than one year to use one or more properties repeatedly for recreation or housing aims for a definite period of time. As for the characteristics of the right of utilization acquired by timeshare agreement, from the aspect of using this right, there is the direct and indirect type: in the first case apart from the title nothing is needed in order to use timeshare, but in the latter case a legal instrument (e.g. membership in an organization) must be applied beside the title in order to live with the right of utilization (the right of utilization is attached to the mentioned legal instrument). The direct right of utilization can be considered as right in rem, contract law and it can be special right of use. The economy prefers the character of right in rem of the timeshare because it is attached to the quality characters (value) of that thing as an article in use. During the regulation of timeshare agreements in Europe the protection of the consumer came into the limelight (see: Scandinavian countries, Benelux states, United Kingdom, Germany, Austria, Hungary, Serbia, Croatia, Bosnia Herzegovina, Montenegro, Romania, Czech Republic, Italy) or the market and tax law aspect became important (see: Greece, Portugal, Spain, France). There is a chaotic situation of timeshare in Europe: similarly to the Hungarian legal situation, in many other European states the private law must face challenges considering the right of use acquired by timeshare agreement, only few countries make a stand for only one legal solution.